(untitled) (Baghdad Science Journal, 2021)
Date palm silver nanoparticles are a green synthesis method used as antibacterial agents. Today, there is a considerable interest in it because it is safe, nontoxic, low costly and ecofriendly. Biofilm bacteria existing in marketed local milk is at highly risk on population health and may be life-threatening as most biofilm-forming bacteria are multidrug resistance. The goal of current study is to eradicate biofilm-forming bacteria by alternative treatment green synthesis silver nanoparticles. The biofilm formation by bacterial isolates was detected by Congo red method. The silver nanoparticles were prepared from date palm(khestawy) fruit extract. The formed nanoparticles were characterized with UV-Vis and AFM. The antibacterial activity of synthetic silver nanoparticles was evaluated by agar well diffusion method. Gram-negative bacteria isolates were E. coli in 3 isolates and Klebsiella pneumoniae in 5 isolates and all are biofilm producer. The size of synthetic green silver nanoparticles is 18 nm and the generation of silver nanoparticles was confirmed by change of date extract color from yellow to brown with an absorption maximum at 410 nm. Highly antibacterial activity of silver nanoparticles was recorded in comparison to plant extract and silver nitrate against gram-negative biofilm-forming bacteria. From this study, the antibacterial activity of date palm silver nanoparticles was more efficient to eradicate gram negative biofilm[1]forming bacteria isolated from marketed local milk